Use of the international classification of headache disorders, Second Edition, criteria in the diagnosis of primary headache in schoolchildren: Epidemiology study from eastern Turkey - (:unkn) unknown (My University, 2010)
We aimed to determine the prevalence of primary headache among schoolchildren in the city of Agri, located in eastern Turkey, where geographical, climatic and socio-economic conditions differ greatly from those of other regions of Turkey. A cross-sectional school-based (ages ranging from 11 to 18) study was conducted from January to April 2006. Diagnosis was based on the second edition of the International Classification of Headache Disorders. This population was evaluated by a two-stage clustered sampling procedure. In the first phase, 1385 children were asked whether they had had a headache within the past year. For the second-step interview, 540 children (38.9%) with a complaint of headache were selected. Five children who had complained of headaches in the first interview did not agree to participate in the second stage. Of the remaining 535, 473 were identified as having primary headache and 62 as having secondary headache. Overall, one-year prevalence of headache subtypes was 14.3% for migraine, 3.5% for probable migraine, 8.6% for pure tension-type headache, 4.6% for migraine plus tension-type headache, and 3.0% for probable migraine plus tension-type headache. The prevalence of migraine was higher in our study than in previous studies. © International Headache Society 2010.
Keywords: adolescent; epidemiology; migraine; prevalence; Primary headache; tension-type headache